Generation and delivery of free hydroxyl radicals using a remote plasma. (1st January 2023) - McQuaid, H N; Rutherford, D; Mariotti, D; Maguire, P D
Abstract: We demonstrate a new gas-based O H ∙ generation source using a low power radio frequency driven atmospheric pressure plasma configured to deliver the radical flux into the far effluent region, well away from interference from other plasma factors such as electric fields, currents, and ultraviolet radiation. Using He–H2 O gas chemistry isolated from the laboratory air, the plasma generated flux contains O H ∙ and other radicals including, O and HO2 as well as H2 O2 which, along with, was found to vary with H2 O vapour content and absorbed power density. Peak flux values were 2.3 nmol s −1 and 0.23 nmol s 1 for H2 O2 and O H ∙ respectively at a distance of 50 mm from the plasma, with 790 ppmv H2 O and a power density of ∼10 8 W m −3 . The maximum O H ∙ flux density was 4.5 × 10 19 m −2 s −1 falling to 1.7 × 10 19 m 2 s 1 at 110 mm, equivalent to generation rates of 74 µ M s 1 and 28 µ M s −1 . Despite high O H ∙ recombination rates at the plasma exit, the escaping flux is still significant, indicating a viable delivery capability to downstream targets. Its performance with regard to O H ∙ generation rates compares well with traditional O H ∙ generation techniques such as radiolysis, advanced oxidation processes and enhanced Fenton-chemistry approaches where O H ∙ production rates are sub- µ M s −1 . Delivering precisely quantifiable O H ∙ fluxes provides new opportunities for scientific studies and technological opportunities in cell biology, atmospheric chemistry, protein unfolding and systematic dose studies for plasma-based and other O H ∙ related potential medical treatments.